Genotypic diversity alters invasive ability of Hydrocotyle verticillata - Ma, Yao-Le; Li, Wei-Long; Huang, Lin; Xue, Wei; Yu, Fei-Hai (Frontiers in Plant Science, 2025)
Genetic diversity is a key component of biodiversity and plays an important role in shaping ecosystem structure and function. However, how genetic diversity of alien plants may influence their invasive ability requires further empirical investigation. In a greenhouse experiment, we planted a population of the alien plant Hydrocotyle verticillata consisting of 1, 2, 4 and 8 different genotypes in a native plant community to investigate the effects of genotypic diversity of alien plants on performance of both the alien plants and native plant communities. Shoot biomass of H. verticillata increased with increasing the number of genotypes, peaking at the 2-genotype treatment. By contrast, genotypic diversity did not influence the aboveground biomass or evenness of the native plant communities. Moreover, we found that the net genotypic diversity effects decreased with increasing the number of genotypes, and it was negatively correlated with the aboveground biomass of the native plant communities. These effects were attributed to the presence of particular genotypes in the mixed-genotype treatments. These results indicate that genotypic diversity of alien plants can alter their invasive ability through selection effects.